Characteristics of breast cancer in Central China, literature review and comparison with USA. (December 2016) - Chen, Chuang; Sun, Si; Yuan, Jing-Ping; Wang, Yao-Huai; Cao, Tian-Ze; Zheng, Hong-Mei; Jiang, Xue-Qing; Gong, Yi-Ping; Tu, Yi; Yao, Feng; Hu, Ming-Bai; Li, Juan-Juan; et al.
Abstract: Introduction: This work was to analyze characteristics of breast cancer (BC) in Central China, summarize main characteristics in China and compare with USA. Methods: BC main characteristics from four hospitals in Central China from 2002 to 2012 were collected and analyzed. All the single and large-scale clinical reports covering at least ten years were selected and summarized to calculate the BC characteristics of China. BC Characteristics in USA were selected based on the database from Surveillance, Epidemiology, and End Results (SEER) Program. Results: Age distribution in Central China was normal with one age peak at 45–49 years, displaying differences from USA and Chinese American with two age peaks. BC characteristics in Central China displayed distinct features from USA and Chinese American, including significant younger onset age, lower proportion of patients with stage I, lymph node negative, small tumor size and ER positive. A total ten long-term and large-scale clinical reports were selected for BC characteristics of Mainland China analysis. A total of 53, 571 BC patients were enrolled from 1995 to 2012. The main characteristics of BC in Mainland China were similar as that in Central China, but were significant different from developed regions of China (Hong Kong and Taiwan), USA and Chinese American. Conclusions: BC characteristics in Central China displayed representative patterns of Mainland China, while showed distinct patterns from Chinese patients in other developed areas and USA. Highlights: Main characteristics of breast cancer patients in Central China displayed representative patterns of Mainland China. Main characteristics of breast cancer patients in Central China displayed distinct patterns of Chinese American. Main characteristics of breast cancer patients in Mainland China displayed distinct patterns of Chinese American. Main characteristics of breast cancer patients in Mainland China displayed distinct patterns of Hong Kong and Taiwan.